Fault Diagnosis of Grinding Machine Using Choi-Williams Distribution Based on COM Module Technology - Sun, Miao Zhong; Xu, Yuan Li; Wang, Chuan (Applied Mechanics and Materials, 2012)
In this paper, a time-frequency analytic system is implemented by using mixed programming of Matlab and Delphi languages based on COM (Component Object Model）module technology. Matlab possesses many signal analytic functions and Delphi has a friendly visual programming environment. These two advantages are fully combined in the mixed programming. This system can be easily upgraded to expand new analytic functions with help of COM module technology. Fault diagnosis of a grinding machine is carried out by using this system. A same vibrational signal sampled from the machine is analyzed in turn by three methods in this system that are Fast Fourier Transform(FFT), Wigner-Ville Distribution(WVD) and Choi-Williams Distribution(CWD). Comparing with the three results, it shows that CWD can get best diagnostic information and validity of the estimation on the instantaneous frequency of a signal. Success of the mixed programming is presented meantime.